Challenges associated with systemic therapy for older patients with inoperable non-small cell lung cancer. (21st November 2020) - O'Leary, Connor; McSorley, Lynda; Hennessy, Bryan; Grogan, Liam; Breathnach, Oscar; Morris, Patrick
ABSTRACT: Introduction: Lung cancer is the most common cancer diagnosed worldwide. Data from several studies fall short to make appropriate conclusions on the management for elderly patients. The discovery of targeted therapy and immunotherapy has allowed these patients access to a wider array of options. Areas covered: The authors review research for treating older patients with lung cancer focusing on research performed in this patient population. Data are presented relating to chemotherapy, immunotherapy, and targeted therapy in the advanced setting. Expert opinion: Elderly patients particularly benefit from advances in systemic therapy. Based on the tumor profile, treatment with targeted therapy or immunotherapy should be favored over chemotherapy where possible in the elderly population. Elderly patients benefit from EGFR, ALK, and ROS-1 inhibition in the setting of these tumor alterations. These agents should be utilized early in the treatment course. Across many studies, the benefit from immunotherapy is seen irrespective of age. Favorable outcomes and toxicity profiles from immunotherapy compared to chemotherapy are well described. Chemotherapy should be offered with caution after a detailed assessment. Options include combination or single-agent chemotherapy regimens. Best supportive care alone is a reasonable option in the frailer, highly co-morbid patient.